Architecture for health. Construction of the Dos de Mayo Hospital in Lima - Barrera, Henry (2023)
This research analyzes the importance of the construction of Dos de Mayo Hospital in the mid-nineteenth century in the progress and improvement of health in Lima. The need to build it arose as a result of the increase in the population in the city, the growth in the number of patients, the arrival of yellow fever at the beginning of 1868 and the lack of comfort in the hospitals in operation. Dos de Mayo represented the strengthening of the professional and scientific sense of institutions of this type. Through the review of hemerographic sources of the time, the concern to reform the hospital service and improve patient care is observed; in other words, to guarantee one of the fundamental rights of every human being, the right to life.